(untitled) (Economic and Political Thought, 2018)
General Data Protection Regulation (GDPR) was a response to more and more common use of personal data in commercial transactions. The Regulation is aimed at standardising the provisions at the supranational level and increasing consumer protection. GDPR has a potential for influence on the global standards and practices of personal data processing. Will the new legislation be able to address another type of global challenges connected with the use of big data by politicians and public authorities? Recent events, especially those concerning the use of advanced analysis of data in Donald Trump’s electoral campaign and the campaign of Brexit supporters’, show the need for guarantees of reliability, stability and security of democratic processes.